Targeted trade policy instruments and climate change mitigation: The case of environmental provisions in trade agreements - Petros Suzgo Kayovo Mkandawire; Dela-Dem Fiankor; Bernhard Brümmer (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
This article explores the effects of including environmental provisions (EPs) in preferential trade agreements (PTAs) on climate change mitigation. It further examines whether the effects depend on the heterogeneity of the EPs. We exploit a panel dataset of the climate change performance index (CCPI) from 2006 to 2019 and the environmental performance index (EPI) from 2000 to 2020 for multiple countries. We combine these datasets with the TREND database that contains information on almost 300 different types of EPs in 775 PTAs. Empirically, we use an autoregressive panel data model with an exponential fractional regression framework and a two-step system generalized method of moments (GMM) estimator. Potential endogeneity issues are addressed with suitable instrumentation and panel estimation techniques. Our results shows that the inclusion of EPs in PTAs significantly improves climate change mitigation. The effectiveness of these provisions, however, depends on their diversity. Key benefits include reduced greenhouse gas emissions, increased renewable energy use, and enhanced climate policies. Furthermore, PTAs with direct CPs yield greater improvements in climate change mitigation outcomes compared to those addressing environmental issues more generally or indirectly. Finally, we show that PTAs with climate change provisions are an effective tool for climate change mitigation, regardless of the development status of the signatories. However, the effects are more pronounced for North-South PTAs compared to North-North and South-South PTAs.
Keywords: F13; F18; Q54; Q56; 330; Trade agreements; environmental provisions; climate change; environmentalhealth; environmental policy; climate change performance index